Science and Technology Opportunities in Hadith Research - Wahyudin Darmalaksana (International Journal of Islamic Khazanah, 2021)
The purpose of this research is to discuss the opportunities of science and technology in hadith research. This research method uses qualitative research through literature study with a content analysis approach. The results and discussion of this research include the hadith science methodology, the development of the hadith validity method and the hadith text criticism method with a multidisciplinary and transdisciplinary approach, and scientific and technological opportunities in hadith research for the need for integration of science. The conclusion of this study is that research on hadith with a transdisciplinary approach opens wide opportunities for science and technology that are currently developing for the realization of the integration of science. This study recommends the importance of applying a transdisciplinary approach to science and technology opportunities in the development of hadith research in Islamic higher education